Robots Learning Through Physical Interactive Intelligence - Martín-Martín, Roberto (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Artificial Intelligence (AI) has revolutionized fields like computer vision and natural language processing, yet its impact on robotics remains limited by challenges in long-horizon decision-making and complex physical interactions. My research pioneers robot learning algorithms that exploit (predict, perceive, plan, and reason about) physical interaction as a core component of artificial intelligence, pushing beyond passive solutions in domains such as perception, navigation, and manipulation. By leveraging techniques in imitation learning and hierarchical reinforcement learning, my work empowers robots to learn from human demonstrations, navigate interactively in real-world environments, and gather information through purposeful interactions. In my talk, I will explain how these advances are critical for robots to become useful helpers in human environments, opening the door to the next generation of household robots. I will present several AI algorithmic innovations to integrate physical interactions in computation procedures and outline the path toward developing continually learning robots capable of operating autonomously in unstructured human environments, enhancing their utility as adaptable and intelligent assistants.